Phenotype, Husbandry and Performance of the Taggar Goats in Eldaleng Area, South Kordufan ٍ ◌State, Sudan - Mudawi , Tilal M. A.; Elimam, Mohmed E.; Ahmed, Mohmed Khair A.; Ibrahim, Neama A. E. (University of Khartoum Journal of Agricultural Sciences, 2023)
Tagger goats are a promising meat breed, with excellent conformation and meat quality, in Nuba Mountains, where it is raised under extensive farming conditions. The objectives of this study were to study the phenotypic characteristics, husbandry and reproductive and lactation performance of this genotype in Eldaleng area. Mean body weight was 22.5 kg. Mean body measurements (cm) were 58.75, 65.9, 78.4 and 38.55 for height at withers, heart girth, barrel circumference and back length, respectively. Body weight and measurements were generally significantly (P ≤0.001) higher in males than in females and significantly (P ≤0.001) increased with age. Phenotypic correlations between body weight and measurements were generally high, and different regression equations accurately predicted body weight with no significant differences at all ages. Animal colours varied greatly. Most animals were kept in all goat ages. Flock size was 21.1 and females dominated flocks and their longevity was higher than males. The animals depended on natural pastures and grazed on village outskirts. They kidded all the year round with peaks in April and October. They were weaned at 4.1 months old and most of the males were castrated. Puberty, age at first service and age at first kidding were 7.15, 8.4 and 13.1 months, respectively. Kidding rate was 87%, twining rate was 52.8% and kidding interval was 245.4 days. Mean birth weight was 1.35 kg. Mortality rate was 26.5% in kids and 10.1% in adults. Milk yield was 0.64 kg/day in 156 days.